Proceedings of the 2nd International Conference on Innovative Research Across Disciplines (ICIRAD 2017) 2017
DOI: 10.2991/icirad-17.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Tri Hita Karana - Based Educational Tourism

Abstract: This study was aimed at analyzing and describing the impacts of Tri Hita Karana-Based Educational Tourism on the quality of the community life. This descriptive qualitative research was done to the communities of Mengesta Village. The subjects consisted of 60 community members involved as the learning resource persons in developing the educational tourism. The data which were collected consisted of the impact of the development of educational tourism on the improvement of the community life quality. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The research obstacle of Parwati et al (2017) were also successfully answered through this research by showing a design that facilitates accurate calculations by applying the simple additive weighting method to obtain the effectiveness level from the internalization of Tri Hita Karana concept in determining the indicators that become a priority for improvement so that students' morals and achievements can be better. Validity evidence that the results of this research were able to show the design that facilitates the implementation of the SAW method, which intended can be explicitly seen in Figure 8 specifically in the weighted process, normalization process, and ranking process.…”
Section: Based On Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The research obstacle of Parwati et al (2017) were also successfully answered through this research by showing a design that facilitates accurate calculations by applying the simple additive weighting method to obtain the effectiveness level from the internalization of Tri Hita Karana concept in determining the indicators that become a priority for improvement so that students' morals and achievements can be better. Validity evidence that the results of this research were able to show the design that facilitates the implementation of the SAW method, which intended can be explicitly seen in Figure 8 specifically in the weighted process, normalization process, and ranking process.…”
Section: Based On Tablementioning
confidence: 99%
“…That research has a connection and similarity with this research, namely in terms of integrating ANEKA concepts into indicators of moral assessment and student achievement at IT Vocational schools. The obstacle that was found in the Hilyana and Hakim's research was the absence of the Tri Hita Karana concept which was used as a foundation in controlling the integration of ANEKA values so that ANEKA values were not able to be internalized optimally in the learning process; 3) The research that was conducted by Parwati et al (2017) showed a positive influence from the Tri Hita Karana concept in the learning process, especially in the field of tourism. That research has similarities and relevance to this research in terms of the utilization of the "Tri Hita Karana" concept, namely as a basis for determining judgment standards in the Countenance evaluation model that was used to evaluate the computer learning process of IT Vocational students.…”
Section: Introductionmentioning
confidence: 99%